EFEKTIVITAS MEDIA PEMBELAJARAN TIGA DIMENSI (3D) DALAM MENDUKUNG INOVASI PEMBELAJARAN DI ERA DIGITAL - Kamila Salma Farikha; Nabila El Shafira Aghnia Kusumaningrum; Muhammad Fathikun Naqiya; Surayanah Surayanah (ELEMENTARY: Jurnal Inovasi Pendidikan Dasar, 2026)
Advances in digital technology have spurred the emergence of various learning innovations aimed at improving the quality of the learning process. One widely used innovation is three-dimensional (3D) learning media, as it can present objects in a more concrete, realistic, and interactive manner compared to conventional media. This study aims to analyze the effectiveness of three-dimensional learning media in supporting learning innovations in the digital age. The study employed a literature review method by examining various relevant journals, books, and scientific articles from 2022 to 2026. Data were analyzed based on aspects of conceptual understanding, learning outcomes, motivation, student engagement, and the application of 3D media across various subjects. The findings indicate that 3D learning media is effective in enhancing students’ conceptual understanding, particularly for abstract topics, as it provides more realistic and easily understandable visualizations. Additionally, 3D media has also been proven to enhance student motivation, engagement, and learning outcomes in science, mathematics, and civic education. The integration of technologies such as Augmented Reality (AR) and Virtual Reality (VR) further strengthens the effectiveness of 3D media by providing a more interactive, engaging, and meaningful learning experience. However, the implementation of 3D media still faces challenges in the form of limited resources and teachers’ readiness to manage technology-based learning. Therefore, the use of 3D learning media needs to be optimally designed to support effective, innovative learning that is relevant to the demands of the digital age. ABSTRAK Perkembangan teknologi digital mendorong munculnya berbagai inovasi pembelajaran yang bertujuan meningkatkan kualitas proses belajar. Salah satu inovasi yang banyak digunakan adalah media pembelajaran tiga dimensi (3D) karena mampu menyajikan objek secara lebih konkret, realistis, dan interaktif dibandingkan media konvensional. Penelitian ini bertujuan untuk menganalisis efektivitas media pembelajaran tiga dimensi dalam mendukung inovasi pembelajaran di era digital. Penelitian menggunakan metode studi literatur dengan mengkaji berbagai jurnal, buku, dan artikel ilmiah yang relevan pada rentang tahun 2022–2026. Data dianalisis berdasarkan aspek pemahaman konsep, hasil belajar, motivasi, keterlibatan siswa, serta penerapan media 3D pada berbagai mata pelajaran. Hasil kajian menunjukkan bahwa media pembelajaran 3D efektif dalam meningkatkan pemahaman konsep siswa, terutama pada materi yang bersifat abstrak, karena mampu menghadirkan visualisasi yang lebih nyata dan mudah dipahami. Selain itu, media 3D juga terbukti meningkatkan motivasi, keterlibatan, dan hasil belajar siswa pada pembelajaran IPAS, matematika, maupun PPKn. Integrasi teknologi seperti Augmented Reality (AR) dan Virtual Reality (VR) semakin memperkuat efektivitas media 3D karena memberikan pengalaman belajar yang lebih interaktif, menarik, dan bermakna. Namun, implementasi media 3D masih menghadapi kendala berupa keterbatasan sarana dan kesiapan guru dalam mengelola pembelajaran berbasis teknologi. Oleh karena itu, penggunaan media pembelajaran 3D perlu dirancang secara optimal agar mampu mendukung terciptanya pembelajaran yang efektif, inovatif, dan relevan dengan tuntutan era digital.